The Entry of Islam into the Archipelago: Trade Routes and the Spread of Da'wah - Nida Ghaida Nabilah; Achmad Maftuh; Siti Muasaroh; Fatma Sari; Azzahra Oktaviani (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
The process of the entry of Islam into the archipelago is an important part of the journey of Indonesian history which took place gradually and peacefully. The spread of Islam was not carried out through military force, but through social interaction that was built between Muslim traders, clerics, and local communities. Trade activities became the initial medium for the spread of Islam, especially in coastal areas that had long been connected to international trade routes. Through these interactions, Islamic values are introduced slowly and accepted by the local community. In addition to trade, Islamic da'wah also develops with a cultural approach that adjusts to the social and cultural conditions of the people of the archipelago. Preachers, including Sufi figures, convey Islamic teachings in a persuasive and accommodating way to local traditions, thus creating a harmonious acculturation process. This research aims to examine the process of entry and development of Islam in the archipelago through trade and da'wah channels, as well as analyze the formation of the Islamic pattern of the archipelago. The research method used is a qualitative approach through literature studies on various historical sources and relevant scientific studies. The results of the study show that the combination of trade, cultural da'wah, and education gave birth to Islam Nusantara which is moderate, inclusive, and adaptive to the diversity of Indonesian society until now.